A structural scheme proposal derived from geophysical data in the epicentral area of the Boumerdes (Algeria) earthquake of May 21, 2003 - Samai, Saddek; Idres, Mouloud; Ouyed, Merzouk; Bourmatte, Amar; Boughacha, Mohamed Salah; Bezzeghoud, Mourad; Borges, José Fernando (Elsevier, 2017)
In this study, we processed and interpreted gravity and aeromagnetic data of the epicentral area of the Boumerdes earthquake (May 21, 2003). The joint interpretation of both data allowed the development of a structural scheme that shows the basement undulations offshore and onshore. The shape of the eastern part of the Mitidja Basin is better defined; its northern edge is represented by a large “sub-circular” uplifted basement located offshore. The rise of this basement indicates that this basin does not extend towards the sea. At the eastern part of the study area, aeromagnetic data have revealed that the Sid-Ali-Bounab basement is individualized in a “sub-circular” shape, while the Dellys basement, located in the NE part, is elongated in the NE-SW direction and extends offshore. The aeromagnetic data also highlighted two EW basement uplifts which divide Isser depression into three parts. The northern part of this depression extends offshore. The southernmost uplift is an extension of the Thenia Fault (TF), suggesting the continuity of this fault to the east. It is important to note that the active Reghaia Fault (RF), which runs through the Boudouaou and Reghaia urban centers, is bounded by two faults suggesting that its length does not exceed 12 km. Moreover, alluvial terraces observed west of the active Zemmouri Fault (ZF) are in agreement with the reverse component of this fault.
Keywords: Gravity; Aeromagnetic; Boumerdes earthquake; Basement; Faults